Cultural Studies and Political Economy: Toward a New Integration - Robert E. Babe (Lexington Books, 2009)
This book addresses the notorious split between the two fields of cultural studies and political economy. Drawing on the works of Harold Innis, Theodor Adorno, Raymond Williams, Richard Hoggart, E.P. Thompson, and other major theorists in the two fields, Robert E. Babe shows that political economy can be reconciled to certain aspects of cultural studies, particularly with regards to cultural materialism.